CREDITOR CLAIMS IN THE INSOLVENCY PROCEEDINGS OF A LEGAL ENTITY - Kronis, Ivars (Administrative and Criminal Justice, 2016)
The study “Creditor claims in the insolvency proceedings of a legal entity” contains analysis of the legal norms that prescribe the filing and verification of creditor claims, decisions adopted by administrator concerning creditor claims, as well as the procedure for filing of creditor claims and complaints related to the acknowledging, waiver or partial acknowledging of creditor claims. The issue of creditor claims in the insolvency proceedings of legal entities is studied in details on the basis of the legal regulations and conclusions of application theory and practice. The study contains no analysis of the regulations applicable to the insolvency of the participants of finance and capital market whereas they are supervised in accordance with the requirements of regulatory acts by the Financial and Capital Market Commission and their activities are governed by special legal norms. Even though the issue of creditor claims has been earlier discussed in the insolvency law science of Latvia, authors of the relevant studies have discussed them in brief. This leads to conclusion that the issue of creditor claims is topical and that theoretical and practical study thereof is significant for insolvency law of the present day. Empiric base of the study comprises scientist works and article collection materials, periodical materials and sources, legal acts, Internet resources and other publicly available information. The approaches used in exploring the study include analytical, comparative and deductive research methods. The study is developed with the following structure (the questions of study also represent parts of this work): 1) General description of filing creditor claims; Formal legal requirements applicable to creditor claims; 3) Status of creditor and complaints concerning claims.